Medicament group for synergistically promoting sedimentation and rheological property of high-alkali flotation copper tailings and application

By using a combination of interface regulators of sodium stearate and sodium laurate and anionic polyacrylamide flocculants in copper tailings treatment, the problems of slow settlement rate and poor rheology performance of copper tailings in high alkali environments are solved, and efficient settlement and low energy consumption transportation are achieved.

CN120190047APending Publication Date: 2025-06-24CENT SOUTH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510630383.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-16
Publication Date
2025-06-24

AI Technical Summary

Technical Problem

In a high alkali environment, the sedimentation rate of copper tailings is slow, the solid-liquid separation efficiency is low, and the adsorption efficiency of traditional flocculants is reduced at high pH, ​​resulting in an increase in the volume of the sedimentation object and an increase in the energy consumption of the transport.

Method used

The combination of interface regulator A and flocculant B is adopted. Interface regulator A contains sodium stearate and sodium laurate. Flocculant B is anionic polyacrylamide. The surface of mineral particles is hydrophobic and modified through interface regulator A to reduce negative charge density, weaken electrostatic repulsion, and enhance the bridging efficiency of flocculant.

Benefits of technology

It significantly improves the settlement rate and rheological performance of copper tailings, reduces the moisture content and viscosity of the sediment, reduces the energy consumption of transport, and achieves low-dose and efficient treatment of the agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120190047A_ABST
    Figure CN120190047A_ABST
Patent Text Reader

Abstract

The invention discloses a reagent group for synergistically promoting sedimentation and rheological properties of high-alkali flotation copper tailings and application, and belongs to the technical field of tailings treatment. The agent group comprises an interface regulating agent A and a flocculating agent B; the interface regulating agent A simultaneously contains sodium stearate and sodium laurate; and the flocculant B is anionic polyacrylamide. In the treatment process of the high-alkali flotation copper tailings, an interface regulating agent A and a flocculating agent B are added at the same time to treat fine particles of the copper tailings. The interface regulating agent A is used for copper tailing surface modification, the flocculating agent B is used for copper tailing fine particle aggregation, the copper tailing fine particles are rapidly flocculated and settled through the synergistic effect of the interface regulating agent A and the flocculating agent B, and the rheological property of ore pulp is improved. Through the synergistic effect of the trace interface regulating agent and the flocculating agent, the sedimentation rate of the ore pulp can be effectively increased, meanwhile, the flowability of the ore pulp is improved, the conveying energy consumption of the ore pulp is reduced, and pipeline abrasion is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a reagent group, in particular to a reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings, belonging to the technical field of tailings treatment. Background Art

[0002] Tailings are solid waste generated after ore dressing. Their storage problem has become a technical problem that needs to be solved in the development and utilization of mineral resources in my country. At present, the annual production of tailings in my country has exceeded 1.4 billion tons, of which copper tailings account for about 30%, with an annual output of about 400 million tons, ranking first among non-ferrous metal tailings.

[0003] Copper tailings treatment faces multiple technical challenges. After lime high-alkali flotation treatment, the pH value of the tailings slurry is usually between 10 and 11.5. However, in a high pH environment, the negative charge density on the mineral surface increases, and the electrostatic repulsion between particles increases, making the dispersion of fine particles stronger, the sedimentation rate slows down, and the solid-liquid separation efficiency decreases. At the same time, the solid content of the underflow decreases and the volume increases, further leading to a reduction in the effective storage capacity and service life of the tailings pond.

[0004] In the traditional tailings treatment process, the addition of high molecular weight flocculants such as polyacrylamide or polyaluminium chloride accelerates particle aggregation and is expected to improve the solid-liquid separation efficiency. However, in a highly alkaline slurry environment, the enhanced electrostatic repulsion between mineral particles will also lead to a decrease in the adsorption efficiency of the flocculant. In addition, the high pH value is not conducive to the extension of the long chain structure of the flocculant, reducing the effective interaction between the functional groups of the agent and the particle surface, and further reducing the bridging efficiency of the polymer flocculation. Studies have found that the introduction of coagulants such as quaternary ammonium salts and metal salts to synergize with flocculants or increase the dosage of flocculants to accelerate flocculation, sedimentation and compression, but failed to take into account the maintenance or improvement of the rheological properties of the slurry, resulting in excessive compaction of the bottom flow after sedimentation, and a significant reduction in pipeline transportation efficiency. For example, Zhu et al. pointed out in their study on the effect of polyethylene oxide (PEO) concentration on the flocculation and rheological properties of tailings slurry that within a certain range, as the amount of PEO increases, the underflow solid content is over-compacted, resulting in a sharp increase in the yield stress of the concentrated underflow, see https: / / doi.org / 10.1016 / j.powtec.2023.119002. This shows that although the flocculation effect can be enhanced and the solid content can be increased by increasing the amount of flocculant, the viscosity of the underflow will be increased, which is not conducive to subsequent pumping and pipeline transportation operations.

[0005] Therefore, it is of great significance to develop a reagent group that can synergistically promote the sedimentation and rheological properties of high-alkali flotation copper tailings. On the one hand, it will help improve the sedimentation efficiency of copper tailings and increase the solid content of the sediment; on the other hand, it will improve the rheological properties of the copper tailings sediment, which is expected to reduce the volume of the tailings sediment while reducing the energy consumption of transportation, contributing to the construction of a low-carbon and green mine. Summary of the Invention

[0006] In order to overcome the deficiencies of the prior art, the first object of the present invention is to provide a reagent group that can synergistically promote the sedimentation and rheological properties of high-alkali flotation copper tailings. This reagent group is used in the treatment of high-alkali flotation copper tailings to simultaneously improve the sedimentation performance and rheological properties of copper tailings.

[0007] The second object of the present invention is to provide a method for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings. This method uses a special reagent group to increase the sedimentation rate of copper tailings, improve the fluidity and thixotropy of the pulp, thereby reducing the energy consumption of pulp transportation and the cost of pipeline wear.

[0008] To achieve the above technical objectives, the present invention provides a reagent group that can synergistically promote the sedimentation and rheological properties of high-alkali flotation copper tailings, which includes an interface regulator A and a flocculant B; the interface regulator A contains sodium stearate and sodium laurate at the same time, and the mass ratio of sodium stearate to sodium laurate is 1:0.9 - 1.8; the flocculant B is an anionic polyacrylamide.

[0009] The sodium stearate and sodium laurate contained in the interface regulator A of the present invention have molecules composed of long-chain alkyl groups and carboxyl groups. In a strongly alkaline environment, the carboxyl groups are completely dissociated, and they adsorb on the surface of mineral particles through coordination and electrostatic interactions, and compete with hydroxyl groups (-OH - ) for adsorption sites, significantly reducing the negative charge density on the particle surface, thereby weakening the electrostatic repulsion force and making it easier for particles to aggregate into clusters and settle rapidly. The hydrophobic alkyl chains are arranged in an oriented manner to form a dense hydrophobic layer, reducing the thickness of the hydration film and surface energy between particles. The short carbon chain structure of sodium laurate reduces the viscosity of the pulp, thereby improving the rheological properties of the pulp.

[0010] The interface regulator A and the flocculant B of the present invention have a synergistic effect in the treatment of high-alkali flotation copper tailings. The interface regulator A adsorbs on the surface of copper tailings particles, hydrophobically modifies the surface of mineral particles, weakens their hydration effect, provides more adsorption sites for the flocculant B, and can adsorb more fine particles in the pulp; the interface regulator A also reduces the negative charge density on the mineral surface and weakens the electrostatic repulsion force, thereby enhancing the bridging efficiency of the flocculant B.

[0011] As a preferred scheme, in the interface regulator A, the mass ratio of sodium stearate to sodium laurate is 1:1 - 1.5.

[0012] As a preferred embodiment, the number-average molecular weight Mn of the flocculant B is 8 million to 12 million.

[0013] The interfacial regulator A contains both sodium stearate and sodium laurate as solutes, and the concentration of the solutes is 0.25 wt.% to 1.0 wt.%, preferably 0.25 wt.% to 0.5 wt.%, and more preferably 0.4 wt.% to 0.5 wt.%.

[0014] The mass concentration of the flocculant B is 0.01 wt.% to 0.1 wt.%.

[0015] As a preferred embodiment, in terms of mass parts ratio, the interfacial regulator A:flocculant B = 20 - 80:2 - 3.5.

[0016] For the application of the reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings in the present invention, the interfacial regulator A and the flocculant B are simultaneously added to the high-alkali flotation copper tailings slurry for mixing and pulp conditioning, so that the reagents are in full contact with the mineral particles, rapid flocculation sedimentation is achieved, and the rheological properties of the pulp are improved. The pH of the high-alkali flotation copper tailings slurry is greater than or equal to 10.

[0017] As a preferred embodiment, for the application of the reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings in the present invention, the dosage of the interfacial regulator A in the high-alkali flotation copper tailings slurry is 200 g / t to 800 g / t, preferably 400 g / t to 500 g / t; the interfacial regulator A contains both sodium stearate and sodium laurate as solutes, and the concentration of the solutes is 0.25 wt.% to 1.0 wt.%, preferably 0.25 wt.% to 0.5 wt.%, and more preferably 0.4 wt.% to 0.5 wt.%. The solvent in the interfacial regulator A is water or a water-alcohol mixture.

[0018] As a preferred embodiment, for the application of the reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings in the present invention, the dosage of the flocculant B in the high-alkali flotation copper tailings slurry is 20 g / t to 35 g / t. The flocculant B is added in the form of a solution with a mass concentration of 0.01 wt.% to 0.1 wt.%.

[0019] As a preferred embodiment, for the application of the reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings in the present invention, the pH of the high-alkali flotation copper tailings slurry is 10 - 11.5.

[0020] As a preferred embodiment, for the application of the reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings in the present invention, the concentration of the high-alkali flotation copper tailings slurry is 12 wt.% to 25 wt.%.

[0021] As a preferred embodiment, the application of the reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings in the present invention, in the high-alkali flotation copper tailings slurry, the particle size of the solid particles is 0.3 μm to 225 μm, preferably 0.3 μm to 150 μm.

[0022] As a preferred embodiment, the application of the reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings in the present invention, during the mixing and pulp conditioning process, in the reagent addition and mixing stage: the stirring speed is 600 rpm to 800 rpm, and the time is 2 min to 3 min; in the floc formation stage: the stirring speed is 200 rpm to 400 rpm, and the time is 4 min to 5 min.

[0023] Preferably, the application of the reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings in the present invention includes: continuously adding an interfacial regulator A with a mass concentration of 0.25 wt.% to 1.0 wt.% and a flocculant B with a mass concentration of 0.01 wt.% to 0.1 wt.% to the high-alkali flotation copper tailings simultaneously, performing surface modification on the fine particles of the high-alkali flotation copper tailings, achieving rapid flocculation and sedimentation, and improving the rheological properties of the pulp. Preferably, the dosage of the interfacial regulator A is 200 g / t to 800 g / t, and more preferably 400 g / t to 500 g / t. Preferably, the molecular weight of the anionic polyacrylamide is in the range of 8 million to 12 million, and more preferably 9 million to 11 million; the dosage of the anionic polyacrylamide is 20 g / t to 35 g / t, and more preferably 20 g / t to 30 g / t. The present invention uses anionic polyacrylamide to achieve better flocculation effect on copper tailings. The molecular weight of 9 million to 11 million can not only ensure the excellent flocculation ability of polyacrylamide, but also avoid excessive water wrapped in the flocs caused by too high molecular weight of the reagent, thereby affecting the moisture content of the concentrated underflow. Preferably, during the mixing and pulp conditioning process, in the reagent addition and mixing stage: the stirring speed is 600 rpm to 800 rpm, and the time is 2 min to 3 min; in the floc formation stage: the stirring speed is 200 rpm to 400 rpm, and the time is 4 min to 5 min. In the present invention, appropriate stirring speed and sufficient pulp residence time can enable the particles in the pulp to fully react and adsorb with the interfacial regulator and the flocculant, reducing the consumption and excessive use of the reagent.

[0024] In the present invention, a higher stirring speed is adopted in the reagent addition and mixing stage to quickly mix and fully contact the reagent and the pulp particles, realizing the surface modification treatment of the particles. The speed is reduced to 200 rpm to 400 rpm in the floc formation stage to form flocs at a low speed, avoiding excessive fragmentation of the flocs under high-speed shearing.

[0025] Beneficial technical effects brought by the technical solution of the present invention compared with the prior art:

[0026] The combined treatment agent for efficient sedimentation and pipeline transportation of high-alkali flotation copper mine tailings provided by the present invention has the main principle and advantages as follows: (1) The carboxyl groups in the agent can preferentially occupy the adsorption sites on the surface of mineral particles, destroy the original double-layer structure on the particle surface in the high-alkali pulp environment, reduce the negative charge density on the particle surface, and then weaken the electrostatic repulsion between mineral particles, accelerating the sedimentation rate; (2) The hydrophobic alkane chains in the agent can be arranged directionally on the particle surface, reducing the hydrophilicity and surface energy of the particle surface, reducing the thickness of the hydration film on the mineral surface, thereby reducing the water content of the sedimentation flocs; (3) The special short carbon chain structure of sodium laurate retains part of the hydration film on the surface of the flocs, thereby reducing the viscosity of the sedimentation flocs, improving the rheological properties and apparent viscosity of the tailings sediment, and is expected to reduce the energy consumption during the transportation process; (4) Through the synergistic effect of the long carbon chain of sodium stearate and the short carbon chain of sodium laurate, combined with the bridging effect of anionic polyacrylamide, high-efficiency treatment can be achieved at a low dosage. In summary, for copper tailings in a high-alkaline environment, the present invention optimizes the combination of sodium stearate, sodium laurate, and anionic polyacrylamide, uses anionic polyacrylamide to improve the sedimentation performance of copper tailings, uses the long carbon chain of sodium stearate to reduce the hydrophilicity of the particle surface, and the short carbon chain of sodium laurate to enhance the rheological properties of the sedimentation flocs. The compound use of the three can improve the sedimentation rate while improving the rheology and thixotropy of the pulp, and finally achieve the multi-objective synergistic optimization of high-efficiency sedimentation, low-energy consumption transportation, and reagent reduction in the process of copper tailings treatment. Brief Description of the Drawings

[0027] Figure 1 It is a comparison diagram of the properties of copper tailings pulp under the conditions of Example 1 and Comparative Example 1, where (a) and (b) are the sedimentation and rheological curves of Example 1 respectively; (b) and (d) are the sedimentation and rheological curves of Comparative Example 1 respectively.

[0028] Figure 2 It is a sedimentation process diagram of the pulp system in Example 1. The sediment flocs are larger, which improves the initial sedimentation rate of the tailings pulp system. Detailed Embodiments

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0030] Example 1

[0031] Sedimentation and rheological property experiments were carried out using the tailings of a super-large copper mine in Yunnan. The main minerals in the tailings are quartz, feldspar, chlorite and mica, among which SiO2 is 56.88 wt.%, Al2O3 is 13.20 wt.%, the concentration of the tailings pulp is 22.46 wt.%, and the pH of the tailings pulp is about 11. In the tailings slurry, the particle size of the solid particles is D 10 = 2.20 μm, D 50 = 16.95 μm, D 90 = 64.95 μm.

[0032] The application method of the reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings pulp is as follows: Continuously add an interfacial regulator A with a mass concentration of 0.5 wt.% and an addition amount of 500 g / t to the high-alkali flotation copper tailings pulp to modify the surface of mineral particles, in which the mass ratio of sodium stearate to sodium laurate is 1:1. At the same time, continuously add an anionic polyacrylamide with a mass concentration of 0.05 wt.% and an addition amount of 20 g / t, and its molecular weight is about 10 million, so that the fine particles in the pulp can flocculate and settle quickly, and the rheological properties of the pulp are improved. During the mixing and pulp conditioning process, in the reagent addition and mixing stage: the stirring speed is 600 rpm and the time is 3 min; in the floc formation stage: the stirring speed is 350 rpm and the time is 5 min.

[0033] After testing, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp is 39 cm / min; in terms of rheological properties: the apparent viscosity of the concentrated underflow at 300 rpm is 44.24 mPa·s, and the hysteresis area is 773.24 Pa / s.

[0034] Comparative Example 1

[0035] Other conditions are the same as those in Example 1, except that: the interfacial regulator A was not added to the tailings pulp for surface modification, and only an anionic polyacrylamide flocculant with a mass concentration of 0.05 wt.% and an addition amount of 20 g / t was continuously added, and its molecular weight is about 10 million.

[0036] After testing, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp is 33 cm / min; in terms of rheological properties: the apparent viscosity of the concentrated underflow at 300 rpm is 60.03 mPa·s, and the hysteresis area is 1049.50 Pa / s. Compared with Example 1, the initial sedimentation rate of the tailings pulp slows down by 15.38%, the apparent viscosity of the underflow increases by 35.69%, and the hysteresis area increases by 35.73%.

[0037] Comparative Example 2

[0038] Other conditions were the same as those in Example 1, except that: the surface modifier A with a mass concentration of 0.5 wt.% and a dosage of 500 g / t was continuously added to the tailings pulp to modify the surface of mineral particles, where the mass ratio of sodium stearate to sodium laurate was 1:1, and then the anionic polyacrylamide flocculant with a mass concentration of 0.05 wt.% and a dosage of 20 g / t and a molecular weight of about 10 million was continuously added.

[0039] After testing, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp was 35 cm / min; in terms of rheological properties: the apparent viscosity of the thickened underflow at 300 rpm was 46.34 mPa·s, and the hysteresis area was 829.07 Pa / s. Compared with Example 1, the initial sedimentation rate of the tailings pulp slowed down by 10.26%, the apparent viscosity of the underflow increased by 4.75%, and the hysteresis area increased by 7.22%.

[0040] Comparative Example 3

[0041] Other conditions were the same as those in Example 1, except that: the usage method of the reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings was: sodium stearate with a mass concentration of 0.5% and a dosage of 500 g / t was continuously added to the high-alkali flotation copper tailings pulp, and at the same time, anionic polyacrylamide with a mass concentration of 0.05 wt.% and a dosage of 20 g / t and a molecular weight of about 10 million was continuously added.

[0042] After testing, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp was 36.5 m / min; in terms of rheological properties: the apparent viscosity of the thickened underflow at 300 rpm was 52.46 mPa·s, and the hysteresis area was 812.63 Pa / s. Compared with Example 1, the initial sedimentation rate of the tailings pulp slowed down by 6.41%, the apparent viscosity of the underflow increased by 18.58%, and the hysteresis area increased by 5.09%.

[0043] Comparative Example 4

[0044] Other conditions were the same as those in Example 1, except that: the usage method of the reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings was: sodium laurate with a mass concentration of 0.5 wt.% and a dosage of 500 g / t was continuously added to the high-alkali flotation copper tailings pulp, and at the same time, anionic polyacrylamide with a mass concentration of 0.05 wt.% and a dosage of 20 g / t and a molecular weight of about 10 million was continuously added.

[0045] After testing, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp is 33 cm / min; in terms of rheological properties: the apparent viscosity of the thickened underflow is 49.06 mPa·s at 300 rpm, and the hysteresis area is 854.47 Pa / s. Compared with Example 1, the initial sedimentation rate of the tailings pulp slows down by 15.38%, the apparent viscosity of the underflow increases by 10.90%, and the hysteresis area increases by 10.51%.

[0046] Comparative Example 5

[0047] Other conditions are the same as those in Example 1, except that the flocculant continuously added to the tailings pulp is cationic polyacrylamide.

[0048] After testing, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp is 29.5 cm / min; in terms of rheological properties: the apparent viscosity of the thickened underflow is 64.32 mPa·s at 300 rpm, and the hysteresis area is 817.38 Pa / s. Compared with Example 1, the initial sedimentation rate of the tailings pulp decreases by 24.36%, the apparent viscosity of the underflow increases by 45.39%, and the hysteresis area increases by 5.71%.

[0049] Comparative Example 6

[0050] Other conditions are the same as those in Example 1, except that the flocculant continuously added to the tailings pulp is non-ionic polyacrylamide.

[0051] After testing, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp is 45 cm / min; in terms of rheological properties: the apparent viscosity of the thickened underflow is 52.06 mPa·s at 300 rpm, and the hysteresis area is 1060.40 Pa / s. Compared with Example 1, although the initial sedimentation rate of the tailings pulp increases by 15.38%, the apparent viscosity of the underflow increases by 17.68%, and the hysteresis area increases by 37.14%, failing to achieve the synergistic promotion effect of sedimentation performance and rheological properties.

[0052] Example 2

[0053] The difference from Example 1 is that the pH of the high-alkali flotation copper tailings pulp is about 10, and the usage method of the reagent group is the same.

[0054] After testing, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp is 33 cm / min; in terms of rheological properties: the apparent viscosity of the thickened underflow is 34.95 mPa·s at 300 rpm, and the hysteresis area is 452.33 Pa / s.

[0055] Comparative Example 7

[0056] Other conditions were the same as those in Example 2, except that: Instead of adding interfacial regulator A to the tailings pulp for surface modification, only an anionic polyacrylamide flocculant with a mass concentration of 0.05 wt.% and a dosage of 20 g / t was continuously added. Its molecular weight was about 10 million.

[0057] After testing, in terms of sedimentation performance: The initial sedimentation rate of the tailings pulp was 32 cm / min; in terms of rheological properties: The apparent viscosity of the thickened underflow at 300 rpm was 37.46 mPa·s, and the hysteresis area was 458.86 Pa / s. Compared with Example 2, the initial sedimentation rate of the tailings pulp slowed down by 3.03%, the apparent viscosity of the underflow increased by 7.18%, and the unit hysteresis area increased by 1.44%.

[0058] Example 3

[0059] The difference from Example 1 was that: Interfacial regulator A with a mass concentration of 0.5 wt.% and a dosage of 500 g / t was continuously added to the high-alkali flotation copper tailings pulp to conduct surface modification on mineral particles, where the mass ratio of sodium stearate to sodium laurate was 1:1.5. At the same time, an anionic polyacrylamide with a mass concentration of 0.05 wt.% and a dosage of 20 g / t was continuously added. Its molecular weight was about 10 million, enabling the fine particles in the pulp to rapidly flocculate and settle, and improving the rheology of the pulp.

[0060] After testing, in terms of sedimentation performance: The initial sedimentation rate of the tailings pulp was 39 cm / min; in terms of rheological properties: The apparent viscosity of the thickened underflow at 300 rpm was 45.02 mPa·s, and the hysteresis area was 711.95 Pa / s.

[0061] Comparative Example 8

[0062] Other conditions were the same as those in Example 3, except that: Interfacial regulator A with a mass concentration of 0.5 wt.% and a dosage of 500 g / t was continuously added to the high-alkali flotation copper tailings pulp to conduct surface modification on mineral particles, where the mass ratio of sodium stearate to sodium laurate was 4:1. At the same time, an anionic polyacrylamide with a mass concentration of 0.05 wt.% and a dosage of 20 g / t was continuously added. Its molecular weight was about 10 million.

[0063] After testing, in terms of sedimentation performance: The initial sedimentation rate of the tailings pulp was 37 cm / min; in terms of rheological properties: The apparent viscosity of the thickened underflow at 300 rpm was 59.38 mPa·s, and the hysteresis area was 947.29 Pa / s. Compared with Example 3, the initial sedimentation rate of the tailings pulp slowed down by 5.13%, the apparent viscosity of the underflow increased by 31.90%, and the hysteresis area increased by 33.06%.

[0064] Comparative Example 9

[0065] Other conditions were the same as those in Example 3, except that: an interfacial regulator A with a mass concentration of 0.5 wt.% and a dosage of 500 g / t was continuously added to the high-alkali flotation copper tailings pulp to modify the surface of mineral particles, where the mass ratio of sodium stearate to sodium laurate was 1:4. At the same time, an anionic polyacrylamide with a mass concentration of 0.05 wt.% and a dosage of 20 g / t was continuously added, and its molecular weight was about 10 million.

[0066] Upon detection, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp was 37 cm / min; in terms of rheological properties: the apparent viscosity of the thickened underflow at 300 rpm was 50.88 mPa·s, and the hysteresis area was 783.50 Pa / s. Compared with Example 3, the initial sedimentation rate of the tailings pulp slowed down by 5.13%, the apparent viscosity of the underflow increased by 13.02%, and the hysteresis area increased by 10.05%.

[0067] Example 4

[0068] A sedimentation and transportation performance experiment was carried out using the tailings of a super-large copper mine in Jiangxi. The main minerals in the tailings were quartz, chlorite, and calcite, among which SiO2 was 64.56 wt.%, Al2O3 was 14.60 wt.%, the concentration of the tailings pulp was 20.95 wt.%, and the pH was about 11.2. In the tailings slurry, the particle size of the solid particles was D 10 = 2.70 μm, D 50 = 12.05 μm, D 90 = 57.62 μm.

[0069] The application method of the reagent group for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings pulp was as follows: an interfacial regulator A with a mass concentration of 0.5 wt.% and a dosage of 500 g / t was continuously added to the high-alkali flotation copper tailings pulp to modify the surface of mineral particles, where the mass ratio of sodium stearate to sodium laurate was 1:1. At the same time, an anionic polyacrylamide with a mass concentration of 0.05 wt.% and a dosage of 30 g / t was continuously added, and its molecular weight was about 10 million, so that the fine particles in the pulp could flocculate and settle quickly, and the rheological properties of the pulp were improved. During the mixing and pulp conditioning process, in the reagent addition and mixing stage: the stirring speed was 600 rpm and the time was 3 min; in the floc formation stage: the stirring speed was 350 rpm and the time was 5 min.

[0070] Upon detection, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp was 19 cm / min; in terms of rheological properties: the apparent viscosity of the thickened underflow at 300 rpm was 92.87 mPa·s, and the hysteresis area was 1431.20 Pa / s.

[0071] Comparative Example 10

[0072] It is different from Example 4 in that the added flocculant is cationic polyacrylamide.

[0073] After testing, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp is 12 cm / min; in terms of rheological properties: the apparent viscosity of the thickened underflow at 300 rpm is 78.16 mPa·s, and the hysteresis area is 914.65 Pa / s. Compared with Example 4, although the apparent viscosity of the underflow decreases by 15.84% and the unit hysteresis area decreases by 36.10%, the initial sedimentation rate of the tailings pulp slows down by 36.84%, and the synergistic promotion of sedimentation performance and rheological properties is not achieved.

[0074] Comparative Example 11

[0075] It is different from Example 4 in that the added flocculant is non-ionic polyacrylamide.

[0076] After testing, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp is 26 cm / min; in terms of rheological properties: the apparent viscosity of the thickened underflow at 300 rpm is 110.87 mPa·s, and the hysteresis area is 1892.40 Pa / s. Compared with Example 4, the initial sedimentation rate of the tailings pulp increases by 36.84%, but the apparent viscosity of the underflow decreases by 19.38% and the hysteresis area increases by 32.45%, and the synergistic promotion of sedimentation performance and rheological properties is not achieved.

[0077] Example 5

[0078] It is different from Example 4 in that the pH of the high-alkali flotation copper tailings pulp is about 10.

[0079] After testing, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp is 8 cm / min; in terms of rheological properties: the apparent viscosity of the thickened underflow at 300 rpm is 81.05 mPa·s, and the hysteresis area is 1641.00 Pa / s.

[0080] Comparative Example 12

[0081] Other conditions are the same as those in Example 5, except that: the tailings pulp is not surface-modified with the interfacial regulator A, and only an anionic polyacrylamide flocculant with a mass concentration of 0.05 wt.% and a dosage of 20 g / t is continuously added to the tailings pulp, and its molecular weight is about 10 million.

[0082] After testing, in terms of sedimentation performance: the initial sedimentation rate of the tailings pulp is 6.5 cm / min; in terms of rheological properties: the apparent viscosity of the thickened underflow at 300 rpm is 85.45 mPa·s, and the hysteresis area is 1790.10 Pa / s. Compared with Example 1, the initial sedimentation rate of the tailings pulp slows down by 18.75%, the apparent viscosity of the underflow increases by 5.43%, and the hysteresis area increases by 9.09%.

[0083] In the present invention, the copper mine tailings are surface-modified by the interface regulator A, and the flocculant B is used to achieve rapid agglomeration, which not only improves the sedimentation rate of the tailings pulp, but also improves the fluidity of the thickened underflow to reduce the transportation energy consumption and improves its thixotropy. The specific manifestation of improving the sedimentation performance of the tailings pulp is to increase the initial sedimentation rate of the pulp; the specific manifestations of improving the fluidity and thixotropy are to reduce the apparent viscosity and the hysteresis area of the pulp, respectively.

[0084] As mentioned above, it is only the preferred specific embodiment of the present invention and some cases in the technical exploration process of the present invention. However, the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed by the present invention should be covered by the protection scope of the present invention. Therefore, the protection scope of the present invention should be subject to the protection scope of the claims.

Claims

1. A reagent set for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings, characterized in that: The drug group includes an interface regulator A and a flocculant B; the interface regulator A contains sodium stearate and sodium laurate at the same time, and the mass ratio of sodium stearate to sodium laurate is 1:0.9-1.8; and the flocculant B is anionic polyacrylamide.

2. The reagent set for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings according to claim 1, characterized in that: In the interface regulator A, the mass ratio of sodium stearate to sodium laurate is 1:1-1.

5.

3. The reagent set for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings according to claim 1, characterized in that: The number average molecular weight Mn of the anionic polyacrylamide in the flocculant B is 8 million to 12 million.

4. The reagent set for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings according to claim 1, characterized in that: The interface regulator A contains sodium stearate and sodium laurate as solutes, and the concentration of the solutes is 0.25wt.%~1.0wt.%, preferably 0.25wt.%~0.5wt.%, and more preferably 0.4wt.%~0.5wt.%; The mass concentration of the flocculant B is 0.01 wt.%~0.1 wt.%.

5. The reagent set for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings according to claim 4, characterized in that: Calculated by mass ratio, interface regulator A: flocculant B=20~80:2~3.

5.

6. An application of a reagent set for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings as claimed in any one of claims 1 to 5, characterized in that: The interface regulator A and the flocculant B are simultaneously added into the high alkali flotation copper tailings slurry for mixing and slurry adjustment. The pH of the high alkali flotation copper tailings slurry is greater than or equal to 10, preferably 10-11.

5.

7. The use of a reagent set for synergistically promoting the sedimentation and rheological properties of high-alkali flotation copper tailings according to claim 6, characterized in that: The dosage of the interface regulator A in the high alkali flotation copper tailings slurry is 200g / t~800g / t, preferably 400g / t~500g / t; the interface regulator A contains solutes sodium stearate and sodium laurate at the same time, and the concentration of the solute is 0.25wt.%~1.0wt.%, preferably 0.25wt.%~0.5wt.%, and further preferably 0.4wt.%~0.5wt.%; the solvent in the interface regulator A is water or a water-alcohol mixture; The dosage of the flocculant B in the high alkali flotation copper tailings slurry is 20g / t~35g / t; the flocculant B is added in the form of a solution with a mass concentration of 0.01 wt.%~0.1 wt.%.

8. The use of a reagent set for synergistically promoting sedimentation and rheological properties of high-alkali flotation copper tailings according to claim 6, characterized in that: The concentration of the high alkali flotation copper tailings slurry is 12wt.%~25wt.%.

9. The use of a reagent set for synergistically promoting sedimentation and rheological properties of high-alkali flotation copper tailings according to claim 6, characterized in that: In the mixing and slurrying process, the agent is added into the mixing stage: the stirring speed is 600rpm~800rpm, the time is 2min~3min, and the floc formation stage: the stirring speed is 200rpm~400rpm, the time is 4min~5min.

10. The use of a reagent set for synergistically promoting sedimentation and rheological properties of high-alkali flotation copper tailings according to claim 6, characterized in that: include: The interface regulator A with a mass concentration of 0.25wt.% to 1.0wt.% and the flocculant B with a mass concentration of 0.01wt.% to 0.1wt.% are continuously added to the high alkali flotation copper tailings to modify the surface of the fine particles of the high alkali flotation copper tailings, achieve rapid flocculation and sedimentation, and improve the rheological properties of the slurry. The addition amount of the interface regulator A is 200g / t to 800g / t, and more preferably 400g / t to 500g / t; the flocculant B anionic polyacrylamide is 0.01wt.% to 0.1wt.%; the surface of the fine particles of the high alkali flotation copper tailings is modified to achieve rapid flocculation and sedimentation, and improve the rheological properties of the slurry. The molecular weight is in the range of 8 million to 12 million, and more preferably 9 million to 11 million; the dosage of anionic polyacrylamide is 20g / t to 35g / t, and more preferably 20g / t to 30g / t; in the mixing and slurrying process, the agent is added to the mixing stage: the stirring speed is 600rpm to 800rpm, and the time is 2min to 3min; in the floc formation stage: the stirring speed is 200rpm to 400rpm, and the time is 4min to 5min.

Citation Information

Cited By

  • Composite flocculant for sedimentation of fine ore grains and application of composite flocculant

    CN121754924A